1988
DOI: 10.1021/ac00154a018
|View full text |Cite
|
Sign up to set email alerts
|

Effects of selected alcohols on cyclodextrin inclusion complexes of pyrene using fluorescence lifetime measurements

Abstract: This study focuses on the Inclusion complexes of 7-cyclodextrln with pyrene as Indicated by fluorescence lifetime measurements and the effects of alcohols on these systems. The pyrene complex has a longer lifetime than free pyrene, yet quenching Is observed In the presence of 7-cydodextrln.This apparent conflict Is discussed. Also, short-chain alcohols participate In the pyrene/7-cyclodextrln inclusion complexes producing a longer lifetime of the pyrene complex. This participation is described through evaluati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0
1

Year Published

1988
1988
2014
2014

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(25 citation statements)
references
References 35 publications
1
23
0
1
Order By: Relevance
“…The results of this work along with others [5][6][7][8][9][10][11][12] lead to the conclusion that the solvent is very important factor for the guestcyclodextrin complexation process and, generally, in organic solvents the stability constants tend to be smaller [13][14][15]. Nevertheless, Patonay [16][17][18] determined larger binding constants (K int ) for pyrene with -and -CD, in the presence of 10% of tert-butanol in comparison with water. These authors also demonstrated that certain hydrocarbons are very soluble in a DMSO/water mixture, and are more strongly bonded to -CD that in the water.…”
Section: Introductionsupporting
confidence: 59%
“…The results of this work along with others [5][6][7][8][9][10][11][12] lead to the conclusion that the solvent is very important factor for the guestcyclodextrin complexation process and, generally, in organic solvents the stability constants tend to be smaller [13][14][15]. Nevertheless, Patonay [16][17][18] determined larger binding constants (K int ) for pyrene with -and -CD, in the presence of 10% of tert-butanol in comparison with water. These authors also demonstrated that certain hydrocarbons are very soluble in a DMSO/water mixture, and are more strongly bonded to -CD that in the water.…”
Section: Introductionsupporting
confidence: 59%
“…Warner and co-workers have examined the photophysical properties of pyrene in the presence and absence of ,,(-cyclodextrins and selected alcohols (47,48). They evaluated the effect of complexation on fluorescent lifetime and the enhancement or quenching of the observed fluorescence.…”
Section: Luminescence and Chemiluminescencementioning
confidence: 99%
“…The most used cyclodextrin is b-CD, due to the size of its cavity (0.78 nm internal diameter and 0.78 nm height) [4] and its electrochemical stability [5]. CDs are also known for their ability to form inclusion complexes with a variety of guests [6][7][8], especially with n-alcohols, since the cavity of b-CD is somewhat larger than the diameter of the methyl group, 0.4 nm [9].…”
Section: Introductionmentioning
confidence: 99%